New University Law: need to reevaluate university teaching after age seventy. - Orellana Cuellar, Laura (2015)
Last year Act No. 30220 which establishes parameters to improve university education was approved. She has raised concerns in the educational and medical students of our Faculty flat. When analyzing Chapter VIII of the Act which states the powers of Teachers, Article 84 states that the maximum age to practice teaching in a public university is seventy. Those who exceed this age limit may only exercise the extraordinary teaching and teachers. It also prevents them from exercising any administrative office (1). And the extraordinary teachers (emeritus, fees and the like) may not exceed 10% of the total number of teachers of the chair in the respective semester.